THE EFFECTIVENESS OF LEMON JUICE (Citrus limon) ON PURKINJE CELL OF WHITE MALE MICE (Mus musculus) CEREBELLAR CORTEX THAT EXPOSED BY MONOSODIUM GLUTAMATE (MSG) - Afsari, I Gusti Ayu Novita; Fitriani, Hikmah; Suroso, Triono Adi (Proceedings of the International Conference on Applied Science and Health, 2019)
Introduction: A number of studies have indicated that excessive MSG (Monosodium glutamate) consumption can lead to the formation of free radicals that can have a negative effect on purkinje cells in the cerebellar cortex. Lemon fruit is a plant that has benefits as a natural antioxidant because it contains compounds such as flavonoids, vitamin C, citric acid and other substances. This study aims to examine the effect of lemon juice (Citrus limon) to purkinje cells of the cerebellum cortex on male white mice (Mus musculus) which exposed of monosodium glutamate.Method: This research is an experimental laboratory with a post test only control group design. The research  subjects were 30 white male mice divided into 5 groups: normal control given standard  feed, negative control  given MSG dose 4mg / grBW, group of dose I , dose II , and dose III that were each given lemon juice with doses 3.33ml / kgBW, 6.67ml / kgBW, 13.33ml/ kgBW respectively. The number of purkinje cells is calculated in the cerebellar cortex by HE staining. The results of the study were analyzed by One Way ANOVA followed by the Bonferroni Post hoc test.Results: The average number of purkinje cells in administration of lemon juice with dosages of 3.33 ml/kgBW, 6.67 ml/kgBW and 13.33 ml /kgBW were 14.10 cells, 16.73 cells and 17.50 cells respectively. Based on the Post Hoc test, the average number of purkinje cells at the dose of 13.33 ml / kgBW was higher than the negative control (p = 0.021)Conclusion: Lemon juice could be used to reduce negative effect of MSG on purkinje cells of white male mice. Moreover, this finding could be used as reference on further research of benefit of lemon juice.